Hubungan Tingkat Literasi Kesehatan Terhadap Kepatuhan Minum Obat Dan Kualitas Hidup Penderita Hipertensi Di Polresta Sleman - Yuniar Fatmaningsih; Ria Etikasari; Ahmad Suriyadi Muslim (CV. ALIM'SPUBLISHING, 2026)
Hypertension is a chronic disease whose management is substantially determined by an individual's capacity to access and utilize health-related information. Inadequate health literacy may lead to poor medication adherence and diminished quality of life. This study aimed to examine the association between health literacy, medication adherence, and quality of life among hypertensive patients at Polresta Sleman. An observational analytic quantitative design with a cross-sectional approach was employed, involving 80 respondents selected through purposive sampling. Data were collected using the HLS-ID-SF12, MARS-5, and WHOQOL-BREF instruments. Bivariate analysis was conducted using Pearson correlation, while multivariate analysis applied multiple linear regression. Results revealed that health literacy significantly correlated with medication adherence (r = 0.469; p < 0.05) and quality of life (r = 0.447; p < 0.05). Medication adherence also demonstrated a significant correlation with quality of life (r = 0.615; p < 0.05). Simultaneously, both variables accounted for 41.1% of the variance in quality of life (R² = 0.411; p < 0.05). These findings underscore the importance of jointly improving health literacy and medication adherence as an evidence-based strategy to optimize quality of life in hypertensive patients.